THE ROLE OF COHESION IN RECOUNT TEXTS : A CASE STUDY OF SECOND SEMESTER STUDENTS OF STMIK PROVISI IN ENGLISH 2 WRITING ASSIGNMENT - Shinta, Qorinta (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
This study is a descriptive research aiming at discovering to what extent students applied cohesion in recount texts in their writing assignment. The participants were STMIK PROVISI students taking English 2. Data were taken from students’ writing assignments in June 2008 and they were gathered by applying qualitative methods. Results indicated that most students were relatively aware of the stages in recount texts even though some of them applied past and present tenses interchangeably without any logical reasons. Referring to cohesive devices, the students mostly used anaphoric reference, personal reference, and demonstrative reference, as well as simple additive conjunction.